EXPERIMENTAL RESEARCH MODELS IN THE STUDY OF LIVER PATHOLOGY AFFECTING PREGNANCY OUTCOMES - Толибова, Гулрухсор Хайбуллоевна; Крышня, Марина Александровна; Мозговая, Елена Витальевна (Medicine in Kuzbass, 2025)
The degree and intensity of the effects of pregnancy on the hepatobiliary system in the scientific literature still remain a subject for research. Until now, there is a correlation between liver function and the outcome of pregnancy: even moderate changes in liver function indicators (both before pregnancy and in the early stages) can lead to complications that prevent a successful pregnancy, childbirth and the birth of a healthy child.In this regard, the development of experimental models reproducing liver damage in animals is of indisputable interest. When analyzing experiments on pregnant individuals, induction by toxic substances, which are the most effective models, naturally leads both to detect characteristic biochemical disorders that occur when exposed to a toxic agent, and to search for new drugs with hepatoprotective properties.Experimental studies aimed at studying various pathologies of the hepatobiliary system will make the risks of pregnancy disorders in women measurable, and monitoring can be an important step to prevent morbidity and preserve the health of the population by reducing extremely negative consequences for fetal development.
Keywords: liver diseases during pregnancy; experimental liver lesions in rats; types of hepatotoxins; models of liver damage in pregnant animals